Effect of perceived discrimination on depressive symptomatology: The role of avoidant coping in an LGBTQ+ community in Peru - Dionicio-Pinto, Fredy Y. (2025)
He study examines the mediating role of avoidant coping in the relationship between perceived discrimination and depressive symptomatology among 159 members of an LGBTQ+ community in a city in Peru, aged 18 to 52 years (M=28.24, SD=7.85). The Perceived Discrimination Scale in the LGBTQ+ Community by González-Rivera and Pabellón-Lebrón (2018), Spielberger’s (2008) State-Trait Depression Inventory (IDER), and Carver et al.’s (1989) avoidant coping dimension were administered. The results indicate that the mediation models analyzed are satisfactory (CFI=1.00; SRMR<.060). Individual discrimination has a positive effect on state depression (β=.14, p<.05) and trait depression (β=.15, p<.05); similarly, group discrimination has a positive effect on state depression (β=.24, p<.05) and trait depression (β=.20, p<.05). Avoidant coping mediates the relationship between both forms of discrimination and state and trait depression (β>.15, p<.05), confirming the mediation hypotheses. The study confirms that avoidant coping plays a significant mediating role in the relationship between perceived discrimination and depressive symptomatology in members of the LGBTQ+ community in Peru. These findings highlight the importance of addressing coping strategies to mitigate the negative impact of discrimination on the mental health of this population.